The Influence of Career Development and Position Promotion on Employee Work Enthusiasm at the Regional Representative Council Office of Bengkulu Province - Amelia Wahyuni; Ida Ayu Made ER Meytha Gayatri; Yudi Irawan Abi (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2023)
The existence of career development is also needed by every employee to increase work commitment to human resources. The purpose of this study was to determine the effect of career development on employee morale at the DPRD Bengkulu Province Office and to determine the effect of promotion on employee morale at the Bengkulu Provincial DPRD Office and to find out the influence of career development and promotion of positions on employee morale at the DPRD Bengkulu Province Office. This research is a type of quantitative research. The data collection method uses a questionnaire. Furthermore, so that the respondents' answers can be measured, the respondents' answers are given a score. In scoring, a Likert scale is used (Sugiyono, 2015: 168). Based on the results of this study it was concluded that career development (X1) has an effect on employee morale (Y) because the tSig value for the variable (X1) is 0.002. So it can be concluded that tSig<Sig(0.002<0.05) and tcount>ttable (3.963>1.66980) means that Ha is accepted and H0 is rejected, that variable X1 affects Y. Promotion (X2) has an effect on employee morale (Y) because the tSig value for the variable (X2) is 0.001. So it can be concluded that tSig<Sig (0.001<0.05) and tcount>ttable (3.759>1.66980) means that Ha is accepted and H0 is rejected Career development (X1), Promotion (X2) has a positive and significant effect on employee morale (Y) Simultaneously because F count is greater than F table, namely 5.428 > 3.15 and Fsig < 0.05 (0.004 < 0.05